2023
DOI: 10.3390/jcm12134272
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Cancellous Bone versus Injectable Bone Substitute for Endoscopic Treatment of Simple Bone Cyst and Intraosseous Lipoma of the Calcaneus and Is Intraosseous Lipoma a Developmental Stage of a Simple Bone Cyst?

Abstract: Simple bone cysts (SBCs) and intraosseous lipoma (IOL) of the calcaneus are rare tumor entities that are primarily diagnosed due to unspecific heel pain, incidental findings, or rarely due to pathological fractures. Compared to traditional open tumor resections, endoscopic resection of these benign tumors aims to minimize surgical morbidity and maximize surgical efficiency without compromising safety. Grafting is regularly performed to reduce the risk of recurrence and stimulate osseous consolidation of the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…The two new cases of IOL were both located in their pathognomonic location, Diard's area 6, between the major trabecular groups of the calcaneus, where Toepfer et al described all lipoma of bone in their series [10,25]. Interestingly, several studies have demonstrated that IOL can develop from SBC and might be considered a developmental stage of SBC, often times showing cystic and lipomatous changes next to each other on preoperative MRI, intraoperative endoscopic visualization, and a postoperative histopathologic analysis [26][27][28]. This explains why only the age of the patient and not the location within the foot skeleton differs between SBC and lipoma of bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two new cases of IOL were both located in their pathognomonic location, Diard's area 6, between the major trabecular groups of the calcaneus, where Toepfer et al described all lipoma of bone in their series [10,25]. Interestingly, several studies have demonstrated that IOL can develop from SBC and might be considered a developmental stage of SBC, often times showing cystic and lipomatous changes next to each other on preoperative MRI, intraoperative endoscopic visualization, and a postoperative histopathologic analysis [26][27][28]. This explains why only the age of the patient and not the location within the foot skeleton differs between SBC and lipoma of bone.…”
Section: Discussionmentioning
confidence: 99%
“…Other entities that usually do not require biopsy include SBC or IOL of the calcaneus, as imaging with plain radiographs and MRI is so typical that histopathological confirmation of the diagnosis is usually not required [64]. Still, critical size (Pogoda criteria), pain, or tumour anxiety can warrant surgery [28,65] for SBC or IOL [28,65]. If a suspicious lump or bump of the foot and ankle cannot be further distinguished using imaging diagnostics, a histopathological analysis through open or image-guided biopsy must be pursued [9,42].…”
Section: Discussionmentioning
confidence: 99%